METHODS OF DIAGNOSING VEHICLE DIESEL INJECTORS - Vrublevskyi, O.; Lasynovych, B.; Врублевский, А. Н.; Ласинович, Б. Б.; Врублевський, О. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
The results of the method, of diesel injector state estimation are presented. On the basis of the hydrodynamic accumulator of the fuel supply process, there were obtained recommendations on the selection of design and adjusting parameters of the stand for checking the injectors. The criteria for quantitative estimation of diesel engine injector estimation are determined.
МЕТОДИКА ДИАГНОСТИРОВАНИЯ ФОРСУНКИ ТРАНСПОРТНОГО ДИЗЕЛЯ
МЕТОДИКА ДІАГНОСТУВАННЯ ФОРСУНКИ ТРАНСПОРТНОГО ДИЗЕЛЯ
Keywords: diesel fuel system; fuel system; bench tests; diagnostics; mathematical model; injector; determining the state of the injector; дизельная топливная система; математическая модель; стендовые испытания; определение состояния форсунки; дизельна паливна система; математична модель; стендові випробування; форсунка; 621.43.052